Enhancing Accountability Leadership within the South African Police Service - (:unkn) unknown (My University, 2025)
A key component of success in today's fast-paced environment is accountability leadership, as transparency and trust are vital. Although the emphasis on accountability leadership in particular may be more recent, the fundamental ideas are rooted in a number of different leadership theories. This study looks at how accountability leadership might help the South African Police Service (SAPS) become more effective and win back the public's trust. Principal Subjects: frameworks for accountability leadership theory (such as procedural justice theory and social learning theory). A growing body of research has examined several leadership philosophies, such as ethical and authentic leadership, to promote accountability. The SAPS faces several challenges in adopting accountable leadership, including resource restrictions, community participation, and leadership commitment. SAPS accountability mechanisms are now in place (CPFs, IPIDs). Suggestions for enhancing accountability leadership methods (community involvement, openness, and training). Gaps in the body of knowledge now available and potential future study areas. Principal arguments: the SAPS has a promising structure in accountability leadership to address challenges of public trust and improve police performance. Implementing accountable leadership can be guided by combining theoretical frameworks with useful tactics. Moreover, the lack of accountable leadership within the SAPS has a ripple effect, negatively impacting public safety, trust in law enforcement, and the overall effectiveness of the police service. There are significant obstacles to overcome, but doing so with effective leadership, education, and community involvement can pay off. This study uses a literature review methodology, examining previous academic publications on police reform, accountable leadership, and the South African environment. The significance of this study is to contribute to a more moral, efficient, and reliable SAPS by p
Keywords: African Research